Implementasi Pemanfaatan Platform Merdeka Mengajar Pada Guru SMP Di Daerah 3 T (Terdepan, Terluar Dan Tertinggal) - Koli Mela, Angela Graciana; Zulaikha, Siti; Rugaiyah, Rugaiyah (Universitas Negeri Makassar, 2025)
To improve the quality and competence of teachers today, various applications and platforms are provided to support additional teacher knowledge. One of them is the independent teaching platform which is a platform that must be used by teachers because it is able to become a reference in conducting learning. This research study is very important to find out the success of the implementation of the independent teaching platform which is a tool to support the independent curriculum. This research uses a case study qualitative research method. Researchers describe or portray a real event, namely the implementation of the utilization of the merdeka Mengajar platform by junior high school teachers in the 3 T areas (underdeveloped, outermost and foremost). Through comprehensive analysis, case studies allow researchers to explore the variables that influence an event, activity, or process, so as to obtain a comprehensive picture of the case under study. Overall, the implementation of the Merdeka Mengajar (PMM) Platform at SMPN Piebulak provides significant benefits in improving teachers' abilities to design, implement, and evaluate technology-based learning. Despite facing technical and non-technical challenges, especially related to limited internet networks and teachers' time management, PMM still succeeds in promoting learning quality improvement.